Effects of Rainfall Attenuation on Frequencies 1 and 3 GHZ in Nigeria (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Mobile communications are part of our everyday life. The non-ideal environment which is filled with many attenuation factors affects the electromagnetic waves, which radio communication depends. This study considers the spectral range of 1 and 3GHz. At these frequencies, interesting phenomena due to rain are supposed to happen. The study of this frequency spectrum has been undertaken in an attempt to evaluate the frequency dependence of rain effects on electromagnetic waves. The study of rain effects on communication presented in this study relied solely on rainfall data collected from Nigeria Metrological Agency (NiMet) station in Lagos, Nigeria. The months for January to December for 1981-2011 were summed together and the averages were determined. The average is then used to calculate the rain rate and rainfall attenuation using the extracted results for all the locations (Bauchi, Ikeja, Jos, Kebbi, Maiduguri and Warri). The results show that Warri has the highest rainfall rate followed by Lagos. Kebbi and Maiduguri has the least while Jos and Bauchi demonstrated moderate rainfall rates. This also deduced that attenuation has less impact on lower frequencies but increase with higher frequencies. The study reveals that at higher frequencies, the rainfall attenuation is observed to be greater.